Innate immune receptor clustering and its role in immune regulation - Li, Miao (J Cell Sci, 2021)
The discovery of receptor clustering in the activation of adaptive immune cells has revolutionized our understanding of the physical basis of immune signal transduction. In contrast to the extensive studies of adaptive immune cells, particularly T cells, there is a lesser, but emerging, recognition that the formation of receptor clusters is also a key regulatory mechanism in host–pathogen interactions. Many kinds of innate immune receptors have been found to assemble into nano- or micro-sized domains on the surfaces of cells. The clusters formed between diverse categories of innate immune receptors function as a multi-component apparatus for pathogen detection and immune response regulation. Here, we highlight these pioneering efforts and the outstanding questions that remain to be answered regarding this largely under-explored research topic. We provide a critical analysis of the current literature on the clustering of innate immune receptors. Our emphasis is on studies that draw connections between the phenomenon of receptor clustering and its functional role in innate immune regulation.